Pemanfaatan Limbah Organik Pada Budidaya Tanaman Sayuran Menuju Pertanian Yang Ramah Lingkungan di Kabupaten Polewali Mandar - Suryani Dewi; Ikawati Karim; Dian Utami Zainuddin; Andi Werawe Angka (LPPM UNINUS, 2022)
The vegetable crop cultivation in Polewali Mandar Regency has a great opportunity due to the high market demand for vegetable products. Environmental issues are a global concern for the competitiveness of agricultural products. The quality of organic agriculture or environmentally friendly product has become a concern for consumers regarding food safety, health, and long-life habituation. The farming community in Galung Lombok village, Tinambung District, Polewali Mandar Regency depends highly on the use of synthetic chemical fertilizers and pesticides. On the other hand, harvest waste, household waste and coconut water as a byproduct of coconut processing have not been utilised effectively. Thus, this community service program aimed to utilise household organic waste as organic fertiliser and utilise coconut water as plant growth hormone; as well as educate farmers in implementing environmentally-friendly agricultural businesses. The method used were counselling, training, discussion and demonstration to 25 farmers. The program was able to increase the motivation and knowledge of farmers to implement the cultivation of environmentally friendly vegetable crops by using organic fertilizer from household waste and ZPT from coconut water.The vegetable crop cultivation in Polewali Mandar Regency has a great opportunity due to the high market demand for vegetable products. Environmental issues are a global concern for the competitiveness of agricultural products. The quality of organic agriculture or environmentally friendly product has become a concern for consumers regarding food safety, health and long-life habituation. The farming community in Galung Lombok village, Tinambung District, Polewali Mandar Regency depends highly on the use of synthetic chemical fertilizers and pesticides. On the other hand, harvest waste, household waste and coconut water as a byproduct of coconut processing have not been utilised effectively. Thus, this community service program aimed to utilise household organic waste as organic fertiliser and utilise coconut water as plant growth hormone; as well as educate farmers in implementing environmentally-friendly agricultural businesses. The method used were counselling, training, discussion and demonstration to 25 farmers. The program was able to increase the motivation and knowledge of farmers to implement the cultivation of environmentally friendly vegetable crops by using organic fertilizer from household waste and ZPT from coconut water.